Infrastrukturalny charakter partycypacji – zróżnicowanie poziomu miejskiej partycypacji na przykładzie warszawskiej Białołęki - Drozdowska, Adrianna; Kościńska, Justyna; Przepiórkowski, Mikołaj; Trepka, Kamil (Studia Socjologiczno-Polityczne. Seria Nowa, 2018)
Local policy in urban areas is a topic frequently undertaken in sociological literature. One of the analyzed areas is “grassroots” activity of citizens. It can be stated that it is developed on many levels: while using social media, participatory budget or getting involved in political organizations. Such activities are undertaken for example in Bialoleka, a district in the north-eastern part of Warsaw. In this paper, the thesis is made that the intensity of the activity is related to development of infrastructure. On the basis of the research carried out in 2015 and 2016, authors argue that the lack of subjective satisfaction with infrastructure boosts social activity and institutional participation while in contrary – the participatory activities may be suppressed and focused on inner integration when such an assessment turns out to be mainly positive.